Tinjauan Yuridis terhadap Implementasi Nafkah dan Kebijakan Poligami dalam Hukum Keluarga Islam: Studi Perbandingan Indonesia dan Thailand - Nafiah Wachidlatul Jannah; Tubagus Farhan Maulana; Muhammad Ilham Barizi (Syakhsiyah Jurnal Hukum Keluarga Islam, 2025)
This study provides a juridical analysis of financial support obligations and polygamy policies in Indonesia and Thailand. In Islamic law, providing financial support (nafkah) is a fundamental obligation of the husband toward his wife and children, as prescribed in the Qur’an and Hadith. While both countries recognize Islamic legal principles, they apply distinct legal frameworks in implementing rules on financial support and regulating polygamy. In Indonesia, marriage is governed by Law No. 1 of 1974 and the Compilation of Islamic Law, which imposes strict limitations on polygamy and clearly defines household financial responsibilities. In contrast, Muslim communities in southern Thailand have legal autonomy to apply Islamic family law, including provisions on marriage and financial obligations. This study adopts a normative juridical method and a comparative legal approach to assess the effectiveness of each legal system and its impact on women's rights within marriage. The findings reveal that, despite shared Islamic foundations, significant differences exist in the mechanisms for resolving disputes concerning financial support and polygamy. These differences are primarily shaped by the respective national legal structures and state-religion relations in each country.